Understanding biology - Mason, Kenneth A.; Duncan, Tod; Losos, Jonathan B. (New York McGraw-Hill, 2024)
"Everyone teaching biology has been affected by the wave of changes sweeping through college instruction. Digital technologies have set off a revolution in how we teach-from online courses and online course management to interactive and adaptive assessment, almost everything we do as instructors has changed. Yet the textbook itself has not changed significantly. In fact, over the last 30 years we have seen the evolution of the encyclopedic text. These tomes of biology were wonderful to catalog information but not necessarily to teach or learn biology in the ever-changing classroom. Understanding Biology is a result of re-imagining how to present biology to the modern student. Our goal is to produce a text that is both more manageable for the faculty and more approachable for the student. The first step was a thorough analysis of the market to determine what is actually being taught in most courses. This helped us determine which content to remove and which to retain. This, our third edition, therefore, maintains the important concepts, supporting information, and depth of coverage to produce content that actually makes up a modern majors biology course. We reduced the number of chapters by combining topics in new and innovative ways, without eliminating any important topics. This has dramatically reduced the length of the text but retained the expected depth and breadth of coverage for a majors text"--Provided by publisher.
Includes index.
AU Novero ( Recommending faculty) AY2022-2023
Keywords: Biology